Kesintasan Pasien Karsinoma Hepatoselular: Sebuah Studi Komprehensif tentang Pengaruh Awitan Dini versus Lambat dan Faktor Determinannya - Achmad, Ibrahim; Jasirwan, Chyntia Olivia Maurine; Rajabto, Wulyo; Abdullah, Murdani; Nababan, Saut Horas H.; Nasution, Sally Aman; Koesnoe, Sukamto; Sari, Nina Kemala (UI Scholars Hub, 2024)
Introduction. The prognosis for patients with Hepatocellular Carcinoma (HCC) is generally poor because most cases are diagnosed at an advanced stage. Several studies indicate that HCC is more prevalent and has a worse prognosis among younger individuals. This study aims to identify and compare the variations in survival rates between early and late-onset HCC patients at Cipto Mangunkusumo Hospital and investigate the factors that impact survival outcomes in both groups. Methods. Retrospective cohort study of HCC patients registered in HCC registry 2015-2022. Survival was visualized using Kaplan-Meier curves. Prognostic factor variables in the Cox Proportional Hazard Regression analysis by backward method in the final model became independent prognostic factors for overall survival. Results. There were 896 subjects. Patients with early onset had a median survival of 2.0 months (95% CI 1.0-2.9), while late-onset patients had a median survival of 4.0 months (95% CI 3.4-4.5) (p=0.021). During the observation period, the incidence of death in early onset was found to be higher compared to late onset (92.9% vs. 87.7%, p 0.032). In the multivariate analysis for early onset, hypertension comorbidity and lack of hepatitis treatment were prognostic factors increasing the risk of death with [HR 3.7 (95% CI: 1.0-12.7)] and [HR 2.4 (95% CI: 0.9-6.2)] (p=0.053). In the multivariate analysis for late onset, prognostic factors increasing the risk of death include AFP levels ≥200 ng/mL [HR 1.2 (95% CI: 1.0-1.5)], liver cirrhosis [HR 1.2 (95% CI: 1.0-1.3)], AJCC stage 4 as the most advanced stage [HR 4.5 (95% CI: 2.2-8.9)], supportive therapy [HR 5.2 (95% CI: 3.9-6.8)], and palliative therapy [HR 1.6 [95% CI: 1.2-2.2)]. Conclusion. The median survival of early-onset HCC patients is lower compared to late-onset ones because the majority are not given curative treatment. Independent prognostic factors in early-onset are hypertension and hepatitis treatment, while in late-onset AFP levels, liver cirrhosis, AJCC stage, and therapy are given.